Diagnosing external iliac endofibrosis by postexercise ankle to arm index in cyclists - Fernandez Garcia, B.; Alvarez Fernandez, J.; Vega Garcia, F.; Terrados Cepeda, N.; Rodriguez Alonso, M. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE: The aim of this study was to determine a noninvasive method of evaluating external iliac endofibrosis in cyclists. METHODS: Eighteen highly trained male cyclists were divided into two groups: a pathology group (PG; 3 professional and 4 elite) and a control group (CG; 6 professional and 5 elite). Mean age was 26 +/- 6.1 yr for the PG and 24 +/- 4.09 for the CG. We studied humeral and tibial posterior pressure by using Doppler ultrasound and the ankle to arm index (AAI) before and after an incremental exercise test, performed on bike-ergometer until exhaustion. A Wilcoxon test was used to compare pressures and AAI in the PG. A Mann-Whitney test was used to compare the PG with the CG. Fisher discriminant analysis was done to obtain a classification of the legs in ill or normal legs. RESULTS: The minimal AAI achieved in the PG was 0.76 +/- 0.13 for the normal leg (NL) and 0.35 +/- 0.04 for the ill leg (IL). We found significant differences (P < 0.01) from the 1st to 4th minute after exercise between the NL and the IL in the PG, and from the 1st to 10th minute after exercise between the IL and CG. We found significant differences in leg pressures between NL and IL in PG from the 1st to 4th minute (P < 0.01), and from the 1st to the 10th minute after exercise between CG and IL in the PG. Through discriminant analysis, we obtained a classification of the legs as ill or normal by applying a mathematical function at each recovery time studied. CONCLUSIONS: AAI and leg pressures response to maximal exercise is a valid and noninvasive method for the evaluation of external iliac endofibrosis.